Research and extension to promote the sustainability of the basic gratns system in the slopes in the area of El Salvador. - Barber, Richard (Agronomía Mesoamericana, 2016)
We analyzed the priorities for research and extension that would allow farmers to leave an adequate residue cover on the soil surface, without dirninishing the availability of livestock fodder. We evaluated: 1. The identification of the minimum percentage residue cover to reduce erosion and to promote sustainability for different slope gradients, soil cropping systems and agroecological zones. 2. The practices to improve soil fertility. 3. The selection of improved varieties of grain crops and studies on their association with legume cover crops. 4. Modifications in the residue management 5. The production of alternative livestock feeds for the dry season, to reduce the pressure on residues from livestock. 6. The training of farmers on the need to adopt rational systems of residue utilization, to ensure greater sustainability. We found that to promote sustainability in grain cropping systems, it is essential to carry out carry research and extension activities related to the management of both livestock and grain crops.